Response of Selected Clones of Cocoa Seedlings in the Nursery Against High Soil Water Content - Adi Prawoto; Mohammad Zainunnuroni; Slameto . (Pelita Perkebunan (a Coffee and Cocoa Research Journal), 2005)
Since 2001 to 2005, cocoa bean price is high, this condition accelerates farmers to plant and enlarger their cocoa areas. The impact of this euphoria is the possibility that the planting area will be more marginal, i.e. high water table or soil with continuously high water content. This study was to evaluate cocoa planting materials tolerant to those condition. The experiment was conducted in glass house of Indonesian Coffee and Cocoa Research Institute using RCBD, replicated 3 times. The treatments were factorial 10 x 4. The propelegitimate seedlings of 10 clones were the first factor, i.e. KW 165, KW 162, DR 2, DRC 16, GC 7, ICS 13, ICS 60, KW 163, Sca 12, and TSH 858. The second factor were soil water content, that were 100% (field capacity = control), 125%, 150%, and 175%. Watering method was gravimetric, once a month the volume was corrected by wet weight of the seedlings. The study was terminated after 5 month old. The result showed that growth of stem diameter, root dry weight and leaf number still normal until soil water content 25% above field capacity. At that condition, seedling dry weight dropped 13% below control, whereas at 175% treatment the decreasing of seedling dry weight was 34% below control. According to seedling and root dry weights, and chlorophyll content, by using cluster analysis it could be obtained a group of seedlings tolerant to high soil water content, i.e. DRC 16, GC 7, and ICS 60. Meanwhile, a group of seedlings susceptible to high water content, i.e. KW 165, KW 163, and DR 2. Stem diameter and chlorophyl content was good indicator for water logging tolerance reaction for cocoa seedling, its correlation to seedling dry weight were positive and tight. Key words: Theobroma cacao, seedlings, waterlogging, growth, chlorophyll.